2021
DOI: 10.1108/yc-06-2021-1347
|View full text |Cite
|
Sign up to set email alerts
|

Do pop-up ads in online videogames influence children’s inspired-to behavior?

Abstract: Purpose Advertising through the videogame has become one of the most effective and prevalent channels of advertisement, especially via pop-up ads – appearing on the screen that interrupts children’s gaming activity. Despite its importance, the effectiveness of pop-up ads and its advertising value in online videogames (O-VGs) to predict children’s inspired-to behavior remains scant. This study aims to investigate the underlying factors that explain the relationship between the four dimensions of pop-up ads and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Purposive sampling was employed since it is a reliable sampling technique used in marketing and social sciences research (Etikan et al, 2016 ). Purposive sampling is essentially a non-probability sampling approach (Abbasi et al, 2021b ), where the researcher applies individual judgment to choose the representative participant population, which is compatible with the aims and objectives of the study. In the current context, purposive sampling allows us to achieve greater access to our target audience for digital gaming.…”
Section: Methodsmentioning
confidence: 99%
“…Purposive sampling was employed since it is a reliable sampling technique used in marketing and social sciences research (Etikan et al, 2016 ). Purposive sampling is essentially a non-probability sampling approach (Abbasi et al, 2021b ), where the researcher applies individual judgment to choose the representative participant population, which is compatible with the aims and objectives of the study. In the current context, purposive sampling allows us to achieve greater access to our target audience for digital gaming.…”
Section: Methodsmentioning
confidence: 99%
“…On the one hand, COVID has undoubtedly been one of the most extensive fronts of study within the field of video games. Research has been carried out on the role of video games in the pandemic [43], anxiety and the effects of video games on children during this period [44][45][46], as well as studies on self-determination during the pandemic and the positive effects of technology during the pandemic [47].…”
Section: Theoretical Framework and State Of Artmentioning
confidence: 99%
“…We found that, among the top content creators in Spanish, we needed to go down to number 20 to find the first woman, and of the first thirty, there were only two women. With the lack of female references among the top content creator positions, the task of imitation is complicated by not finding a variety of characters in which women can see themselves reflected [45]. On the other hand, among e-sports players, we found that only 24.4% are women, which explains the lack of this motivation among the female gender [1].…”
Section: H1mentioning
confidence: 99%
“…Convenience, high computing power, portability and relatively low prices are behind the growth in demand for mobile phones (Balakrishnan and Griffiths, 2018; Bringula et al , 2018). In addition to the growth in mobile phone demand, mobile games’ popularity is growing worldwide (Abbasi et al , 2021; Balakrishnan and Griffiths, 2018; Hsiao and Chen, 2016).…”
Section: Introductionmentioning
confidence: 99%